The Impact of Offender–Victim Cultural Backgrounds on the Likelihood of Receiving Diversion - Warner, Bella (Criminal justice policy review, 2022)
The extent to which both an alleged offender and victim’s cultural background influences how one is processed through the Australian criminal justice system is largely unknown. Such information would provide some insight into the extent of discrimination within the system. To address this question, this study aimed to ascertain whether offender/victim pairings across Indigenous and non-Indigenous cultural backgrounds predicted the likelihood of receiving diversion for first-time offenders. The sample comprised 5,616 young people aged between 10 and 17 years, from the state of New South Wales, charged with (a) an offense eligible for diversion, and (b) a crime against a person. Chi-square analyses and binary logistic regression were employed to determine proportions of inter- and intra-cultural offending and the likelihood of receiving diversion dependant on cultural grouping. Results demonstrated that charges for intra-cultural crime (within cultural group) were more likely to occur than charges for intercultural crime (between cultural groups). Indigenous subjects were more likely to receive a court summons. An Indigenous subject charged with an offense against an Indigenous victim was more than 2 times more likely to receive a court summons compared with a non-Indigenous offense against a non-Indigenous victim. An Indigenous suject charged with an offense against a non-Indigenous victim was also more likely to receive a court summons compared with a non-Indigenous/Indigenous offender/victim dyad. Findings indicate that Indigenous status is clearly impacting decisions to divert regardless of the victim’s cultural background. Further research is recommended to explore the situational reasons that underpin decisions to divert on the ground.